Opportunities for Restorative Justice in the Settlement of Corruption - Mahmud, Ade; Z, Chepi Ali Firman; Syawali, Husni; Zaini, Tiara Azzahra; Wismaya, Indira Ratna (KnE Social Sciences, 2024)
Corruption is a synonym for financial crime which is perceived by the public to be severely punished, so as to make the final justice system for the settlement of corruption cases. A severe punishment even though there are several corruption cases that have harmed the country’s finances in small loses, and opened up opportunities for restoration. This study aims to analyze the criteria for corruption with small state losses that can be restored and the implications of implementing restorative justice for eradicating criminal acts of corruption. This study uses a normative juridical approach by using secondary data related to restorative justice and criminal acts of corruption and then analyzing them using qualitative techniques. The results of the study show that corruption with small losses can be restored if the value of the loss is not more than 1 billion rupiah, the perpetrator does not have an important role in the implementation of the crime and is not a repetition of the crime. The application of restorative justice is believed to have juridical implications in the form of recovering state losses due to corruption. The restoration process can speed up the stages of the case settlement process, making law enforcement cost efficient, it is an alternative choice to reduce the cost of handling cases to be efficient. This reduces the problem of overcapacity in correctional institutions, while socially this concept affects the public’s perception that state losses due to corruption can be returned without punishment. Keywords: corruption, opportunity, restoration